It's All about Timing: The Involvement of Kir4.1 Channel Regulation in Acute Ischemic Stroke Pathology - Milton, Meagan; Smith, Patrice D. (Frontiers in Cellular Neuroscience, 2018)
Acute ischemic stroke (AIS) is a cerebrovascular disease that is predominately caused by a blood clot that limits blood flow and results in neuronal loss. Glial cells, specifically astrocytes, have been shown to support neurons in the area impacted by the stroke. Kir4.1, an inwardly rectifying potassium channel found predominantly on astrocytes, is involved in K+ spatial buffering, glutamate uptake, and water and volume regulation. Due to these properties, Kir4.1 may also be involved in preventing neuronal loss following ischemia. Potassium-starvation results in programmed cell death under ischemic conditions due to autophagic up-regulation. However, recent evidence indicates that the time at which the autophagic pathway is activated determines whether or not it results in cell survival or death following ischemia. Furthermore, the application of rapamycin, an inhibitor of the mammalian target of rapamycin (mTOR) pathway, reduces the amount of cell survival during times that previously resulted in cell survival due to autophagy under normal conditions. This suggests that Kir4.1 may be linked to the activation of the mTOR pathway, due to its ability to maintain potassium homeostasis, resulting in cell survival under ischemic conditions. The current review proposes a potential underlying mechanism, involving Kir4.1, in the pathogenesis of ischemic stroke.